Introduction to computing and computer science with Pascal - Walker, Henry M. (Little, Brown, 1986)
This book provides a solid, integrated introduction to these fundamental topics. designed to go beyound most existing, computing textbooks, this text considers each topic in detail and brings together important relationship between topics.